A Novel Risk Defining System for Pediatric T-Cell Acute Lymphoblastic Leukemia From CCCG-ALL-2015 Group - Liu, Xiaoming; Zou, Yao; Zhang, Li; Guo, Ye; Chen, Yumei; Yang, Wenyu; Chen, Xiaojuan; Wang, Shuchun; Zhang, Yingchi; Ruan, Min; Chang, Lixian; Zhang, Xiaoyan; et al. (Frontiers in Oncology, 2022)
Objective: T-cell acute lymphoblastic leukemia (T-ALL) is a rare hematological malignancy with poor prognosis. The present study aims to identify the precise risk grouping of children with T-ALL. Methods: We analyzed the outcomes for 105 consecutive patients treated using the Chinese Children’s Cancer Group ALL-2015 (CCCG-ALL-2015) protocol registered with the Chinese Clinical Trial Registry (ChiCTR-IPR-14005706) between 2015 and 2020 in our center. Nine of 21 clinical and biological indicators were selected for the new scoring system based on the analysis in this study. Results: The 5-year overall survival (OS), event-free survival (EFS), and disease-free survival (DFS) rates for the 105 patients were 83.1±4.8%, 72.4±5.6%, and 78.4±3.6%, respectively. Based on the new scoring system, 90 evaluable children were regrouped into low-risk (n=22), intermediate-risk (n=50), and high-risk (n=18) groups. The 5-year survival (OS, EFS, and RFS) rates for all patients in the low-risk group were 100%, significantly higher than the rates for those in the intermediate-risk group (91.2±5.2%, 74.4±8.6%, and 82.5±6.2%, respectively) and high-risk group (59.0±13.2%, 51.9±12.4%, and 51.9±12.4%, respectively) (all P values < 0.01). Conclusion: The CCCG-ALL-2015 program significantly improved the treatment outcomes for childhood T-ALL as compared with the CCCG-ALL-2008 protocol. Our new refined risk grouping system showed better stratification among pediatric T-ALL patients and better potential in evaluating therapeutic efficacy.